Moderators and mediators of outcome in treatments for anorexia nervosa and bulimia nervosa in adolescents: A systematic review of randomized controlled trials. Issue 1 (11th September 2019) - Hamadi, Layla; Holliday, Joanna
Abstract: Objective: To critically appraise papers reporting on moderators and mediators of recommended psychological treatments for anorexia nervosa (AN) and bulimia nervosa (BN) in adolescents. Method: A systematic search of databases was conducted including PsycINFO, Embase, MEDLINE, AMED, CINAHL, and the Cochrane Library. Studies were included where a randomized controlled trial (RCT) compared therapies for AN or BN and reported on moderators or mediators of treatment effect. Twenty‐one eligible papers were included, all based on data from eight RCTs. Results: Family therapies were dominant in the literature. Individual or separated treatment appeared superior for families with more difficult relationships, whereas conjoint family treatment appeared to be superior where good family relationships were reported. Where there was greater eating disorder psychopathology in AN, including eating disorder‐related obsessions and compulsions, the response was better to a family approach than to individual therapies. There was some evidence that a family treatment was superior for those engaging in purging behaviors in BN. Measures of family relationships, parental self‐efficacy, and early change emerged as possible mediators; however, the quality of evidence was mixed and the findings, in some cases, arguably circular. Moderator and mediator analyses were underpowered in all studies, with multiple, and post‐hoc, analyses being run, and a broad range of outcome measures used. Discussion: This review recommends that emerging findings are explored further in adequately powered trials of the different recommended therapies, with a move toward focusing on effect sizes. A consensus on acceptable definitions of outcome, including remission and recovery, would benefit future research. Resumen: Objetivo: Evaluar críticamente los artículos que informan sobre moderadores y mediadores de los tratamientos psicológicos recomendados para la anorexia nervosa (AN) y la bulimia nervosa (BN) en adolescentes. Método: Una búsqueda sistemática fue realizada en bases de datos incluyendo PsycINFO, Embase, MEDLINE, AMED, CINAHL y la Bibliotrca Cochrane. Los estudios fueron incluidos cuando un ensayo controlado aleatorio (RCT) comparaba terapias para AN o BN y reportaba en efectos del tratamiento de moderadores o mediadores. Se incluyeron veintiún artículos elegibles, todos basados en datos de ocho RCTs. Resultados: Las terapias familiares fueron dominantes en la literatura. El tratamiento individual o separado parecía superior para familias con relaciones más difíciles, mientras que el tratamiento familiar en conjunto parecía ser superior cuando fueron reportadas buenas relaciones familiares. Cuando hubo una mayor psicopatología de trastorno de la conducta alimentaria en AN, incluyendo obsesiones y compulsiones relacionadas al trastorno de la conducta alimentaria, la respuesta a un abordaje familiar fue mejor que a terapias individuales. Hubo alguna evidencia de que un tratamiento familiar fue superior para aquellos involucrados en conductas purgativas en BN. Las medidas de las relaciones familiares, autoeficacia de los padres y cambio temprano emergieron como posibles mediadores, sin embargo, la calidad de la evidencia fue mixta y los hallazgos, en algunos casos, posiblemente circulares. Los análisis de moderadores y mediadores tenían poca potencia en todos los estudios, con multiples análisis llevados a cabo, y post‐hoc, y un amplio rango de medidas de resultados utilizadas. Discusión: Esta revisión recomienda que los hallazgos emergentes sean explorados más a fondo en ensayos adecuadamente potenciados de las diferentes terapias recomendadas, con un movimiento hacia enfocarse en el tamaño del efecto. Un consenso sobre definiciones aceptables del resultado, incluyendo remisión y recuperación, beneficiaría la investigación futura.